Hybrid-dimensional magnetic microstructure based 3D substrates for remote controllable and ultrafast water remediation. Issue 3 (15th December 2015) - Du, Ran; Feng, Qingliang; Ren, Huaying; Zhao, Qiuchen; Gao, Xin; Zhang, Jin
Abstract : By boosting surface roughness via devising hybrid dimensional magnetic microstructures on 3D substrates, a remote controllable, superhydrophobic/superoleophilic melamine foam (MM-RSF) was obtained, showing magnetic-driven oil sorption behavior and great potential in oil/water separation. Abstract : In the field of water remediation, a 3D hydrophobic material with both remote controllability and high oil adsorption performance is highly desirable. To achieve it, magnetic components and microstructures are most likely involved. However, the simple enrolling of magnetic materials always results in quite low adsorption capacity. Additionally, the control of microstructures on 3D materials is immature, which limits the improvement of water/oil selectivity and oil adsorption speed. Herein, we devised 0D/2D hybrid dimensional magnetic microstructures with a well-defined morphology on melamine foams, which provided magnetism for remote controllability and highly rough surfaces for substantially enhanced water/oil selectivity. Hence, the resultant materials acquired magnetic-driven properties and superhydrophobicity/superoleophilicity simultaneously. Thus, they possess controllable, ultrafast, and high throughput oil uptake ability and high oil/water separation performance. The present strategy may open a new avenue to devise high-performance magnetic 3D assemblies for water remediation.